Pre-clinical allergenicity assessment of IgE epitope-targeted Der p 2 mutants demonstrate potential as hypoallergenic AIT candidates - Pena-Amelunxen, Glorismer; Asghari, Mohadeseh; Khatri, Kriti; Glesner, Jill; Versteeg, Serge A.; van Ree, Ronald; Chapman, Martin D.; Smith, Scott A.; Chruszcz, Maksymilian; Pomés, Anna; Aglas, Lorenz (Frontiers in Immunology, 2025)
BackgroundAdvancements in hybridoma technology have enabled the production of human IgE monoclonal antibodies (hIgE mAb) for successful IgE epitope mapping of major allergens. Here, we assessed the hypoallergenicity of three IgE-epitope mutants (single 4C8 or 2F10, and double 4C8 + 2F10 epitope mutants) of house dust mite allergen (HDM) Der p 2.MethodsHumanized rat basophilic leukemia (huRBL) cells, passively sensitized overnight with either pairs of Der p 2 specific hIgE mAb (2F10, 4C8 or 2G1) or HDM-allergic serum (n=8), were stimulated with either wildtype (WT) Der p 2 or an epitope mutant and mediator release was measured.ResultsNo degranulation was induced upon stimulation with all mutants, when cells were sensitized with pairs of hIgE mAb specific for at least one mutated epitope. HIgE mAb specific for non-mutated epitopes led to mediator release comparable to WT Der p 2, indicating that epitopes recognized by the three different hIgE mAb are not overlapping and that the 3D-structure of the mutants is conserved. The double 4C8 + 2F10 epitope mutant had a significantly reduced maximal mediator release (48.3%) compared to the WT, in cells sensitized with allergic donor serum. Overall, the area-under-the-curve of mediator release curves induced by the mutants was significantly lower (31-65%) compared to WT. When comparing the EC20, the double 4C8 + 2F10 epitope mutant required a 158-fold higher antigen concentration to induce the same extent of mediator release as WT Der p 2.ConclusionDer p 2 epitope mutants display significantly reduced allergenicity. Particularly, the double 4C8 + 2F10 epitope mutant demonstrated a strong potential as a novel AIT vaccine candidate.